Trauma Induces Interleukin-17A Expression on Th17 Cells and CD4+ Regulatory T Cells as Well as Platelet Dysfunction - Hefele, Friederike; Ditsch, Alexander; Krysiak, Niels; Caldwell, Charles C.; Biberthaler, Peter; van Griensven, Martijn; Huber-Wagner, Stefan; Hanschen, Marc (Frontiers in Immunology, 2019)
Background: The organism’s immune response to trauma is distinctively controlled, its dysregulation leading to severe posttraumatic complications. Platelets, CD4+ regulatory T cells (CD4+ Tregs) and T helper 17 (Th17) cells have been identified to participate in the posttraumatic immune response. Unfortunately, little is known about their exact role and potential interdependency in humans. Aims of this clinical trial were to phenotype the human immune response following injury and to identify risk factors rendering the host more susceptible to trauma induced injury. Methods: This non-interventional prospective clinical trial enrolled patients following multiple trauma, follow up was conducted for 10 days. Peripheral blood CD4+Tregs and Th17 cells were analyzed using flow cytometry to determine Interleukin 17A (IL-17A) expression. Hemostasis and platelet function were assessed with rotational thromboelastometry (ROTEM®). Subgroup analysis was conducted for the factors gender, age, and trauma severity. Results and conclusion: This is the first clinical trial to phenotype the immune response following trauma, focusing on platelets and the adaptive immune response. We discovered a novel increased IL-17A expression on Th17 cells and on CD4+ Tregs following trauma and describe the kinetics of the immune response. The IL-17A response on CD4+ Tregs challenges the ascribed role of CD4+ Tregs to be solely counterinflammatory in this setting. Furthermore, despite a rising number of platelets, ROTEM analysis shows posttraumatic platelet dysfunction. Subgroup analysis revealed gender, age and trauma severity as influencing factors for several of the analyzed parameters.